Women’s Representation and Resistance as Depicted in Josephine Chia’s Frog under a Coconut Shell and Arundhati Roy’s The God of Small Things: A Comparative Study - Nurrahmawati, Nurrahmawati; Puspita, Ida (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
This study is aimed to analyze the comparison between women’s representation and resistance in Josephine Chia’s novel Frog under a Coconut Shell from Singapore and The God of Small Things by Arundhati Roy from India. By using a comparative literature approach, the research focuses on the differences and similarities in women’s representation and resistance to get gender equality in Singaporean and Indian society. Chia’s novel tells the story of Soon Neo and her daughter, Josephine, who struggles to get their rights as women in the midst of patriarchal Peranakan culture in Singapore, and Roy’s novel tells the story of Ammu and her twins children, Rahel and Estha, who fight against the social rules in India that are discriminative against women and the Untouchable people (Paravan). The research employed a descriptive qualitative analysis method and the theory of liberal feminism. There are similarities in the representation of women who are considered as second class and become the objects both sexually and economically; and restrained by their patriarchal society and culture. The difference of both novels is in the caste system which regulates women's freedom only reflected in The God of Small Things. From the perspective of liberal feminism, the female characters in both novels show resistance in making decision, education, society, and economy. However, resisting inequality in economy is only reflected in Frog under a Coconut Shell while resisting inequality in society is only reflected in The God of Small Things. The direct resistance is demonstrated in verbal and non-verbal ways.